2016
DOI: 10.1071/an15881
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impacts and resource use from Australian pork production assessed using life-cycle assessment. 1. Greenhouse gas emissions

Abstract: Abstract. Agricultural industries are under increasing pressure to measure and reduce greenhouse gas emissions from the supply chain. The Australian pork industry has established proactive goals to improve greenhouse-gas (GHG) performance across the industry, but while productivity indicators are benchmarked by industry, similar data have not previously been collected to determine supply chain GHG emissions. To assess total GHG emissions from Australian pork production, the present study conducted a life-cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…The protein that soy adds to the pig's diet is essential, but the production of soy is limited in Europe, hence requiring importation from third countries, mainly America and China. In the paper written by Wiedemann et al [77,78] in Australia, the average calculated was 2.1 to 4.5 kg CO 2 eq/kg of LW.…”
Section: Discussionmentioning
confidence: 95%
“…The protein that soy adds to the pig's diet is essential, but the production of soy is limited in Europe, hence requiring importation from third countries, mainly America and China. In the paper written by Wiedemann et al [77,78] in Australia, the average calculated was 2.1 to 4.5 kg CO 2 eq/kg of LW.…”
Section: Discussionmentioning
confidence: 95%
“…As the demand for animal proteins increases, the gap between supply and demand of feed protein will continue to increase. Soybean meal, the major feed plant protein source included in monogastric animal diets, has a large environmental impact due to land and water use to grow soybeans and the large-scale transportation of this commodity (Wiedemann et al, 2016). Soybean meal availability for animal feed can be limited due to its use in human food streams and low productivity; and in Australia most soybean meal is imported from the US and South America (M'Gee, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A recent life cycle assessment study (Wiedemann et al, 2016) suggested that piggery GHG emissions could be reduced by changing housing/manure management systems, with the greatest reductions achieved by installing biogas capture and combined heat and power systems (CAP-CHP), resulting in total emissions reductions up to 64%. Clearly, the wide adoption of biogas capture, treatment and use systems by Australian pork producers would be crucial for the achievement of the proactive industry goals noted above.…”
Section: General Drivers For Biogas Technologymentioning
confidence: 99%
“…Biogas may not need to be upgraded before being burnt in boilers (Table 1. 1). However, at H2S concentrations higher than 1000 ppm, the formation of sulphuric acid is likely to result in serious corrosion (Wellinger et al, 2013).…”
Section: Uses Of Piggery Biogas On-farmmentioning
confidence: 99%
See 1 more Smart Citation